A Free Space Optic/Optical Wireless Communication: A Survey - Basheer Muslih Mahdi; Essa Ibrahim Essa (Universitas Muhammadiyah Yogyakarta, 2022)
The exponential demand for the next generation of services over free space optic and wireless optic communication is a necessity to approve new guidelines in this range. In this review article, we bring together an earlier study associated with these schemes to help us implement a multiple input/multiple output flexible platform for the next generation in an efficient manner. OWC/FSO is a complement clarification to radiofrequency technologies. Notably, they are providing various gains such as unrestricted authorizing, varied volume, essential safekeeping, and immunity to interference.